Norway : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Norway showed exemplary economic performance over the past decade, as reflected in the strong economic growth and low inflation. Executive Directors commended this development, and stressed the need to maintain monetary and fiscal stances, improve efficiency, and corporate governance. They appreciated the Solidarity Alternative policy framework for preserving the competitiveness of the non-oil economy, and employment through a combination of incomes policy and prudent management of the country's oil wealth. They agreed that the country's economic statistics are adequate for surveillance purposes in their coverage, quality, and timeliness.